Electronic transport of Lorentz plasma with collision and magnetic field effects - 吕冲 弯峰 贾默然 李子良 桑海波 谢柏松 (Chinese physics B, 2016)
The electronic transverse transport of Lorentz plasma with collision and magnetic field effects is studied by solving the Boltzmann equation for different electron density distributions. For the Maxwellian distribution, it is shown that transport coefficients decrease as ? increases, ? is the ratio of an electron’s magneto-cyclotron frequency to plasma collision frequency. It means that the electrons are possible to be highly collimated by a strong magnetic field. For the quasimonoenergetic distribution with different widths, it is found that the transport coefficients decrease greatly as εˉ decreases.In particular when the width approaches to zero the transverse transport coefficients are hardly affected by the magnetic field and the minimal one is obtained. Results imply that the strong magnetic field and quasi-monoenergetic distribution are both beneficial to reduce the electronic transverse transport. This study is also helpful to understand the relevant problems of plasma transport in the background of the inertial confinement fusion.